Gas-phase transport and entropy generation during transient combustion of single biomass particle in varying oxygen and nitrogen atmospheres. (26th April 2018) - Wang, Linwei; Karimi, Nader; Paul, Manosh C.
Abstract: Transient combustion of a single biomass particle in preheated oxygen and nitrogen atmospheres with varying concentration of oxygen is investigated numerically. The simulations are rigorously validated against the existing experimental data. The unsteady temperature and species concentration fields are calculated in the course of transient burning process and the subsequent diffusion of the combustion products into the surrounding gases. These numerical results are further post processed to reveal the temporal rates of unsteady entropy generation by chemical and transport mechanisms in the gaseous phase of the reactive system. The spatio-temporal evolutions of the temperature, major chemical species including CO, CO2, O2, H2 and H2 O, and also the local entropy generations are presented. It is shown that the homogenous combustion of the products of devolatilisation process dominates the temperature and chemical species fields at low concentrations of oxygen. Yet, by oxygen enriching of the atmosphere the post-ignition heterogeneous reactions become increasingly more influential. Analysis of the total entropy generation shows that the chemical entropy is the most significant source of irreversibility and is generated chiefly by the ignition of volatiles. However, thermal entropy continues to be produced well after termination of the particle life time through diffusion of the hot gases. It also indicates that increasing the molar concentration of oxygen above 21% results in considerable increase in the chemical and thermal entropy generation. Nonetheless, further oxygen enrichment has only modest effects upon the thermodynamic irreversibilities of the system. Highlights: Chemical irreversibilities dominate the overall generation of entropy. Increasing mole fraction of O2 from 21% to 37% magnifies the irreversibility significantly. Further O2 enrichment does not affect the irreversibility considerably. At low O2 concentration, combustion of volatiles dominate the gaseous transfer processes. At higher O2 concentrations, heterogeneous reactions become more influential.